(untitled) (Research, Society and Development, 2021)
Middle age, the stage of life in which there are transformations that direct the human being towards the old age, takes place, according to the literature, between 40 and 60 years old. During this period, a series of transformations, as important as those that occur in adolescence, marks the individual who experiences this phase. Likewise, it is worth noting that these changes present different characteristics in men and women. That said, this article aims to discuss the crisis of middle age in men, paying attention to the changes that have occurred in terms of physical and psychological aspects, and not least, how they relate to work and retirement. This study consists in a narrative review of the literature, elaborated in a period of 2 months, during which, articles, books and statistical data were consulted in order to elucidate and bring critical reflections on the content covered. It was observed, as main results, that the maturity is a phase of intense questions and reflections, surrounded, above all, by countless transformations in the body, mind and individual psychology. However, although it is a topic that opens the door to different research approaches, there are few current studies dedicated specifically to the midlife crisis in males. Thus, we concluded, at the end of the study, that with the expansion of life expectancy, this period became even more valuable and essential to the quality of life, health, pleasure and self-esteem, that will greatly influence the old age.